ANALYSIS OF PATENT RESEARCH ON IMPROVING THE RECLAMATION STATE OF SALINE SOILS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article analyzes the scientific research results obtained in the field of reducing various salts in saline soils and improving the reclamation state of soils using biomelioration and melioration methods.